BIOLOGI REPRODUKSI TONGKOL LISONG, Auxis rochei rochei (Risso, 1810) DI PERAIRAN SENDANG BIRU, KABUPATEN MALANG, JAWA TIMUR - Arief Setyanto; Dewa Gede Raka Wiadnya; (Menunda Publikasi) (JFMR (Journal of Fisheries and Marine Research), 2017)
The aims of this study are to know some biological reproductive aspects of bullet tuna. Information of its biological reproductive aspects will be useful for managing the bullet tuna fishery. Determining about gonadal maturity level in fish can be completed by macroscopic and microscopic (histology) observation. The study about gonadal matuity level determination of bullet tuna has been done through histological observation. Sampling was done by taken sample from UPT P2SKP Pondokdadap Sendangbiru, from January until March 2018. Species identification follows the FAO standard procedure (species identification sheet) published 2001. A specimen was deposited at Depository Ichtyologicum Brawijaya with code DIB.FISH.11111 002 03. Forklength of the sampled 82 fish range from 20,10 – 27,20. Gonadal samples were cut with microtome machine at 5 mm thickness. The preparates were then analyzed using biological binocular microscope at 40x magnification. The result showed that maturity stage of bullet tuna dominated by TKG IV with 34 %, followed by TKG III (31 %), TKG 1 (28 %), TKG II (5 %) and TKG V (1 %). Lenght at first maturity occured at 23.88 cm and egg diameter were 20,92–367,65 µm.